Rebels and underdogs : the story of Ohio rock and roll - Pirnia, Garin (Red Lightning Books, 2018)
From Cleveland to Cincinnati and everywhere in between, Ohio rocks. Rebels and Underdogs: The Story of Ohio Rock and Roll takes readers behind the scenes to witness the birth and rise of musical legends like the Black Keys, Nine Inch Nails, Devo, the Breeders, Chrissie Hynde of the Pretenders, and many others who got their start in garages and bars across Ohio. Through candid, first-hand interviews, Garin Pirnia captures new stories from national legends like the Black Keys and slow-burn local bands like Wussy from Cincinnati. Discover why Greenhornes' members Patrick Keeler and Brian Olive almost killed each other on stage one night, what happened to the pink guitar Trent Reznor of Nine Inch Nails gave to band member Richard Patrick, why Devo loved the dissonance when they were booed by 400,000 music lovers in England, and so much more! Entertaining, inspiring, and revolutionary, Rebels and Underdogs is the untold story of the bands, the state, and rock itself.